The paradoxical relationship between ligamentum flavum hypertrophy and developmental lumbar spinal stenosis. Issue 1 (December 2016) - Cheung, Prudence; Tam, Vivian; Leung, Victor; Samartzis, Dino; Cheung, Kenneth; Luk, Keith; Cheung, Jason
Abstract Background Ligamentum flavum (LF) hypertrophy is a common cause of lumbar spinal stenosis and is thought to be degeneration-driven. Developmental spinal stenosis (DSS) is characterized by pre-existing narrowed spinal canals and is likely a developmental problem that occurs in childhood. In these cases, the LF may demonstrate different characteristics as compared to degeneration-driven stenosis. Thus, this study aimed to investigate the relationship between histological changes of LF and canal size. Methods Patients who had surgical decompression for lumbar spinal stenosis were prospectively recruited and divided into three groups (critical DSS, relative DSS and non-DSS) based on previously defined anteroposterior bony spinal canal diameter measurements on MRI. The degree of disc degeneration and LF thickness were also measured from L1 to S1. Surgical LF specimens were retrieved for histological assessment of fibrotic grade and area of fibrosis. Results A total of 19 females and 15 males (110 LF specimens) with an overall mean age of 65.9 years (SD ± 9.8 years) were recruited. DSS was found to have a significant negative correlation (p < 0.001) with LF thickness, its fibrotic grade and area of fibrosis (%). Non-DSS exhibited a significant positive relationship with the degree of LF fibrosis. Disc degeneration and LF thickness had no correlation with LF histology. Conclusions Our study is the first to definitively note that degeneration is the cause of LF fibrosis in non-DSS patients; however, in contrast, an inverse relationship exists between canal size and LF fibrosis in DSS patients, suggesting a different pathomechanism. Hence, despite a similar degree of LF thickness, DSS patients have LF with less fibrosis compared with non-DSS patients. Further investigation of the cause of LF changes in DSS is necessary to understand this relationship.